Test of ocean tide loading models on the basis of strain data measured at the Vyhne Tidal Station, Slovakia - BRIMICH, Ladislav; BEDNÁRIK, Martin; BÓDI, Jozef; MENTES, Gyula (Contributions to Geophysics and Geodesy, 2022)
Tidal strain time series recorded at the Vyhne Tidal Station are used to test thirteen different ocean tide loading models. Ten models have been calculated using SPOTL: EOT11a, HAMTIDE11a, OSU.TPXO72atlas, OSU.TPXO72, TPX070, DTU10, CSR4.0, FES2004, FES95.2.1, SCHW1 and three other models were chosen from the Free Ocean Tide Loading Provider (FOTLP) created by Scherneck and Bos: FES2012, FES2014b, GOT00.2. Hourly sampled strain data, corrected for temperature, were subjected to correction for ocean tide loading. The test of models was focused on the diurnal and semi-diurnal tidal harmonic constituents O1, P1, K1 and M2. A negligible difference between the individual global ocean tide loading models was only found mainly due to using different Earth models and Green functions. The amplitude factors for O1, P1, K1 and M2 derived from the measurements are 1.019, 1.226, 0.842 and 1.131, respectively. The average amplitude factors for these tidal components were obtained after ocean load correction using SPOTL routines: 1.121, 1.332, 0.916, 1.283, and in the case of the three models using FOTLP: 1.046, 1.486, 1.067, 1.317. The corrected amplitude factor became closer to the theoretical value only for K1.